Total Physical Response (TPR) Method in Teaching English Classroom Interaction for Young Learners - Jayanti, Sri; Rachmawati, Etika (Universitas Galuh, 2025)
This paper focused on the TPR method as a learning media for English as a foreign language to young learners. This study was designed to investigate the teachers’ experience in using the TPR method as a means of teaching English to young learners. The research design of this study was a narrative inquiry and the participant of this study was an English teacher at one of the non-formal education institutions in Ciamis. The subject of this research were students and an English teacher in non-formal education Ciamis. The data collection included classroom observation and semi-structured interviews. The results of the study found that the TPR method had a positive influence as a means of learning English as a foreign language, particularly when the teacher teaches vocabulary. From the five-question indicators, it can be concluded that the TPR method is also quite effective to be applied as a learning medium for young learners since young learners have a good memory to input the vocabulary that is being taught. Moreover, it is easier for the teacher to provide learning students’ enthusiasm for learning clearly appears that makes the class not boring.